Murilo Mendes, poeta crítico o infinito íntimo - Palhares, Taisa; Amoroso, Maria Betânia 20./21. Jh; Mammi, Lorenzo 1957- (Museu de Arte Moderna de São Paulo, 2023)
From his first meeting with artist Ismael Nery in 1921 until his death, Murilo Mendes (1901-1975) was one of the most influential figures in Brazilian artistic life. He was an art critic, collector, exhibition organizer, and poet. He played a decisive role in the formation of an entire generation of critics and was Mário de Andrade's interlocutor with regard to Rio de Janeiro's art. His critical thinking can be found in newspapers and magazines, in many poems and poetic prose, but only at the end of his life did Murilo organize part of his critical texts in a volume published posthumously, A invenção do finiteʺ. In 1994, his art collection was acquired by Universidade Federal de Juiz de Fora, that created the Museu de Arte Murilo Mendes (MAMM) and since then he has organized exhibitions and publications about the collection.
Exposição realizada no Museu de Arte Moderna de São Paulo de 5 de setembro de 2023 a 28 de janeiro de 2024
Zusätzliches Online-Angebot unter QR-Code abrufbar (Full content of the catalog in English, Vistas da exposição)
Keywords: Mendes, Murilo -- 1901-1975; Kunstkritik; Kunst; Sammlung; Kultur; Brasilien; Ausstellungskatalog -- Museu de Arte Moderna São Paulo -- 05.09.2023-28.01.2024 -- São Paulo; Bildband